Improving Mathematical Reasoning Ability Students Through Strategy Learning Genius - Rifaatul Mahmuzah, (Jurnal Serambi Ilmu, 2024)
This study aims to examine the differences in the improvement of mathematical reasoning abilities of students who received learning with genius learning strategies and students who received conventional learning at SMA Negeri 1 Runding, Subulussalam City. This study used a pre-test post-test control group design. The population in this study were class X students, which consisted of four classes and two classes were taken randomly to be the sample, namely class X2 as the experimental class and class X1 as the control class. The instrument used to obtain research data is in the form of a mathematical reasoning ability test. The statistical test used to analyze the data on increasing mathematical reasoning ability was the free sample t test. The results showed that the increase in the mathematical reasoning ability of students who received learning with the genius learning strategy was significantly better than students who received conventional learning.